Reality, fiction and bioethics in the posthuman world of “Kentukis” by Samanta Schweblin - Navarro-Fuentes, Carlos Alberto (2024)
This work aims to present concepts such as “posthumanism” and “transhumanism”, by establishing connections and differences between them to explain how humanity relates to technology today. The space in which these concepts are communicated is the dystopian novel Kentukis (2015), by the writer Samanta Schweblin. It proceeds by citing situations and extracts from it, by offering a reflection on the future of humanity in accordance with the concepts mentioned above, giving an account of the complex and sublime universe of Kentukis, as well as the relationships between life, subjectivity, identity and fictional characters, on the one hand; and contemporary reality in the 21st century, on the other hand. The above is undertaken by interspersing ethical and bioethical arguments and reflections that directly concern, and in particular the ominous and growing role that technology plays in the daily events of human life.